2019
DOI: 10.1016/j.cmet.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Dihydroorotate Dehydrogenase-Driven Pyrimidine Biosynthesis Restores Tumor Growth of Respiration-Deficient Cancer Cells

Abstract: Graphical Abstract Highlights d Tumorigenesis depends on functional OXPHOS d OXPHOS-derived ATP is not required for tumor formation d DHODH-driven pyrimidine biosynthesis requires CoQ redoxcycling d CoQ redox-cycling via OXPHOS drives tumorigenesis through pyrimidine biosynthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
198
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 93 publications
7
198
3
Order By: Relevance
“…More recent work has implicated DHODH as a regulator of differentiation in certain myeloid leukemias and pancreatic adenocarcinoma (46,47). Furthermore, Bajzikova et al found that de-novo pyrimidine biosynthesis is essential for mouse breast cancer tumorigenesis in a DHODH dependent manner (48). Our work reveals that beyond effects on cell growth in vitro and primary tumor growth, CRC metastatic progression selects for upregulation of pyrimidine biosynthesis.…”
Section: Discussionsupporting
confidence: 51%
“…More recent work has implicated DHODH as a regulator of differentiation in certain myeloid leukemias and pancreatic adenocarcinoma (46,47). Furthermore, Bajzikova et al found that de-novo pyrimidine biosynthesis is essential for mouse breast cancer tumorigenesis in a DHODH dependent manner (48). Our work reveals that beyond effects on cell growth in vitro and primary tumor growth, CRC metastatic progression selects for upregulation of pyrimidine biosynthesis.…”
Section: Discussionsupporting
confidence: 51%
“…This constitutes an irrefutable piece of evidence in favor of the idea that mitochondria must be fully functional to support the growth of cancer cells. Intriguingly, it appears that mtDNA is required for pyrimidine biosynthesis dependent on OXPHOS‐linked dihydroorotate dehydrogenase to overcome cell‐cycle arrest, while mitochondrial ATP generation itself is dispensable for tumorigenesis …”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, it appears that mtDNA is required for pyrimidine biosynthesis dependent on OXPHOS-linked dihydroorotate dehydrogenase to overcome cell-cycle arrest, while mitochondrial ATP generation itself is dispensable for tumorigenesis. 9 Here, we will briefly review current evidence suggesting that pharmacological inhibition of OXPHOS may have anticancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial trafficking between stroma and cancer cells is relevant in tumour initiation and progression 3,8,9 and dysfunctions in the distribution of mitochondria are connected with neurodegenerative diseases, including Alzheimer's disease, Huntington's disease or amyotrophic lateral sclerosis [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%